Determination of Pesticide Residues in Sour Cherry used in the Sour Fruit Juice Production in Tokat provinces - Tarık Balkan; Kenan Kara (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Sour cherry (Prunus cerasus L.) (Rosaceae) is a spring fruits. It is not preferred to be consumed as fresh because it is sour, but it is extremely beneficial for human health. In addition to fresh consumption, it is used in the production of fruit juice, syrup, jam, marmalade, cake and ice cream in the food industry. Sour cherry is grown widely in Tokat and 80-85% of the grown cherries are sold to juice factories. Producers mostly adopt chemical control against pests. In this respect, monitoring pesticide residues on sour cherry is extremely important. This study was carried out to determine the pesticide residue levels in samples taken from sour cherry production areas in Tokat province in 2020. The residue analyses were performed by using QuEChERS method and LC-MS / MS (Liquid Chromatography / Tandem Mass Spectrometer). According to the results, the pesticide residue levels were found below the maximum residue limits (MRL) given in Turkish Food Codex (TFC).